(3QSGdI aj Gdfjd hRjGOJgs
(3ChdgG (B:s
(3bGd GdMcje GYde CQTOfG Gddg Cf gPg bGYOI jYQa efgG RjGOI Gdfjd s
(3BNQgG (B:s
(3jbY HCQV eUQ bfGd TOjO hGddg JYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI HdOjI GdCScfOQjI (B(170( 4) (3H(B) s
Keywords: (3GdLZQGajG h GdHdOGfs